Parental Knowledge, Attitude, and Behavior towards Basic Immunization (Majalah Kedokteran Bandung, 2021)
Immunization, which is usually done by giving vaccinations, is the process of forming immunity in individuals against infectious diseases. The target in the Strategic Plan of the Ministry of Healht of the Republic of Indonesia in 2015-2019 aimed for 93 % of coverage. However, according to the report of the Indonesian Basic Health Survey (IBHR), there is actually a decrease in basic immunization coverage for the period of 2012–2015 when compared to the previous period. This study aimed to determine the correlation between parental knowledge, attitudes, and behavior towards complete course of basic immunization among parents of an elementary school in North Jakarta, Indonesia, in 2018 and 2019. This was a cross-sectional analytical descriptive study involving 110 respondents. Data were obtained through a questionnaire that was distributed to parents that included questions on knowledge, attitude, and behavior towards complete basic immunization. Out of 110 respondents, 70% stated that their child received the full basic immunization course while the remaining 30% stated that their child only received some of the vaccines required in the basic immunization course. There was no correlation, based on the bivariate analytical test, between parental behavior (p = 0.868), parental attitude (p = 0.647), and full course of basic immunization. In contrast, parental knowledge influences whether the child will receive the full course of basic immunization or not (p=0.000).
Keywords: attitude; behavior; complete basic immunization; knowledge